TradeLens-XR - Mohd Zamidi, Siti Nur Qurratuaini; Yuslie, Fakhiratul Yusrah; Khaizol, Nursyamimi; Mohamad, Nur Asyifa’ Zulaikha; Hashim, Nurhaslinda (Universiti Teknologi MARA, Negeri Sembilan, 2025)
TradeLens-XR is the cutting-edge AR-driven solution introduced here, which has the potential to revolutionize air cargo logistics to address critical issues such as cargo damage, communication barriers, safety risks, and handling inefficiencies due to manual processes. The solution combines AR with artificial intelligence (AI), thermal sensing, and contextual translation with AI to provide real-time tracking of cargo, damage detection, situational awareness, and language-based translation. These capabilities are integrated into a glasses-like, hands-free unit that enables air cargo crews to operate more efficiently and safely in dynamic, high-pressure environments. TradeLens-XR brings great benefits to the logistics industry and society as a whole with enhanced safety, reduced human error, improved traceability, and enabling of sustainable and efficient global trade operations. Business opportunities of the innovation across sectors like aircraft maintenance, security screening, emergency response, and infrastructure monitoring, thereby making it a common product for modern air cargo management.